Theoretical and Experimental Substantiation for Applicability of a Damping Layer in a Foundation Slab Placed on Soil Bed - Kiselev Nikita; Pronozin Yakov; Stepanov Maxim; Bartolomey Leonid; Keck Dietmar (MATEC Web of Conferences, 2016)
Authors present the results of studies of innovative foundation structure. The idea of how to increase the operational quality of foundations and reduce the costs due to rational loading of the soil bed is numerically simulated. It is shown that the bending moment in the foundation slab depends on uneven settlements of the soil bed. It is proposed to stabilize the deformable soil bed by the damping layer placed under the slab footing in the zones with minor settlements. Considered is the concept of the damping layer in the foundation slab placed on the soil bed (DLS). The in-situ test for DLS-clayey bed interaction is described. Given are the results obtained after the experiments for DLS performance. The result of DLS implementation in designing the foundation of the 22-storeyed block of flats is considered. The expediency of DLS in comparison to standard foundations is presented.